In vivo dissolution of poorly water-soluble drugs: Proof of concept based on fluorescence bioimaging - Yinqian Yang; Yongjiu Lv; Chengying Shen; Tingting Shi; Haisheng He; Jianping Qi; Xiaochun Dong; Weili Zhao; Yi Lu; Wei Wu (Acta Pharmaceutica Sinica B, 2021)
In vitro‒in vivo correlation (IVIVC) of solid dosage forms should be established basically between in vitro and in vivo dissolution of active pharmaceutical ingredients. Nevertheless, in vivo dissolution profiles have never been accurately portrayed. The current practice of IVIVC has to resort to in vivo absorption fractions (Fa). In this proof-of-concept study, in vivo dissolution of a model poorly water-soluble drug fenofibrate (FNB) was investigated by fluorescence bioimaging. FNB crystals were first labeled by near-infrared fluorophores with aggregation-caused quenching properties. The dyes illuminated FNB crystals but quenched immediately and absolutely once been released into aqueous media, enabling accurate monitoring of residual drug crystals. The linearity established between fluorescence and crystal concentration justified reliable quantification of FNB crystals. In vitro dissolution was first measured following pharmacopoeia monograph protocols with well-documented IVIVC. The synchronicity between fluorescence and in vitro dissolution of FNB supported using fluorescence as a measure for determination of dissolution. In vitro dissolution correlated well with in vivo dissolution, acquired by either live or ex vivo imaging. The newly established IVIVC was further validated by correlating both in vitro and in vivo dissolution with Fa obtained from pharmacokinetic data.